2020
DOI: 10.1210/jendso/bvaa074
|View full text |Cite
|
Sign up to set email alerts
|

Unmasked Testicular Seminoma During Use of Hormonal Transgender Woman Therapy: A Hidden hCG-Secreting Tumor

Abstract: Abstract Management of gender-affirming hormone therapy (HT) in transgender women includes surveillance of testosterone (T) levels. Failure of T to suppress, despite adherence to therapy, warrants additional investigations for unexpected sources of T or factors stimulating T secretion. Possible causes include T or gonadotropin production by an occult neoplasm. Testicular cancer is the most common malignancy affecting biological men aged between 15 and 35 years. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…A tabela 1 apresenta os dados referentes aos casos de CA em FtM após início da hormonioterapia para transição de mulher para homem com uso de hormônios exógenos. 43 30 NR NR NR NR NR Fiez (2019) 44 43 NR NR NR NR NR Wang (2020) 45 69 NR NR NR NR NR Lienhoop (2020) 46 74 + + -NR NR Elshim y(2020) 47 31 NR NR NR NR NR Nehlsen (2020) 48 53 e 2 casos acima de 60 anos. Para obtenção da média de tempo dos indivíduos que apresentaram uso hormonal antes do diagnostico, foram incluídos apenas 24 casos, devido à falta de informações do tempo de administração hormonal nos dois artigos mencionados, isto posto que a média foi de 6,2 entre 1-25 anos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A tabela 1 apresenta os dados referentes aos casos de CA em FtM após início da hormonioterapia para transição de mulher para homem com uso de hormônios exógenos. 43 30 NR NR NR NR NR Fiez (2019) 44 43 NR NR NR NR NR Wang (2020) 45 69 NR NR NR NR NR Lienhoop (2020) 46 74 + + -NR NR Elshim y(2020) 47 31 NR NR NR NR NR Nehlsen (2020) 48 53 e 2 casos acima de 60 anos. Para obtenção da média de tempo dos indivíduos que apresentaram uso hormonal antes do diagnostico, foram incluídos apenas 24 casos, devido à falta de informações do tempo de administração hormonal nos dois artigos mencionados, isto posto que a média foi de 6,2 entre 1-25 anos.…”
Section: Resultsunclassified
“…AR: receptor de androgênio BRCA: genes supressores tumorais CA: câncer DX: diagnóstico ER: receptor de estrogênio HER2: receptor tipo 2 do fator de crescimento epidérmico MtF: homem para mulher NI: não há informações NR: não realizado PR: receptor de progesterona TH: terapia hormonal Em virtude dos resultados da pesquisa foi observado através do gráfico 1 uma comparação dos tipos de CA na população transexual, contendo números de casos, histórico familiar, média da idade e do tempo de exposição a terapia hormonal antes do diagnostico, conforme resultado da pesquisa foi observado que a média de idade foi superior a 40 anos, sendo que, apenas 2 tipos de CA tiveram idade inferior a 30 anos.Gráfico 1 -Análise de tipos de câncer na população transexual Fonte: Elaborado pelo autor (2021)Perante a apresentação dos casos abordados pelos MtF, apenas um caso de CA de mama não relatou uso hormonal antes do diagnóstico18 e três casos relataram uso hormonal antes do diagnostico, mas não forneceram o tempo pelo qual haviam tido com administração do hormônio exógeno, sendo 1 CA de mama18 , 1 CA de próstata 41 e 1 CA de testículo47 . Sobretudo foram incluídos apenas 25 casos para obtenção dos resultados, entretanto a idade média desses indivíduos que desenvolveram CA em geral após uso de hormônios exógenos foi de 53,8 anos entre a idade de 30-75 anos, consistindo em três casos entre 30-40 anos, cinco casos entre 41-50 anos, nove casos entre 51-60 anos e oito casos acima de 60 anos.…”
unclassified
“…Elshimy et al reported a case of a 31 year old transgender woman who was found to have a beta-HCG secreting seminoma because her total testosterone level failed to suppress. 2 Similarly, Wolf- Gould et al reported the case of a 28 year old transgender woman who developed rising testosterone and estradiol levels while on feminizing hormones and was found to have an intratubular germ cell neoplasia (carcinoma in situ), embryonal cell carcinoma. 1 Kobori et al reported on a 30 year old transgender woman who developed a mature testicular teratoma with positive estrogen receptor beta expression while receiving cross-sex hormonal therapy with estradiol and progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, gonadotropin levels are typically low or suppressed, with testosterone levels that remain above goal range along with potentially inadequate feminization on GAFHT. Multiple case reports with testicular cancer have been reported in the literature diagnosed after initiation of GAFHT [ 22-24 ]. These cases were diagnosed due to elevated testosterone levels despite adequate estradiol levels and multiple high-dose anti-androgen medications, with stalled feminization.…”
Section: Gender-affirming Hormone Therapy Preparationsmentioning
confidence: 99%
“…These cases were diagnosed due to elevated testosterone levels despite adequate estradiol levels and multiple high-dose anti-androgen medications, with stalled feminization. Low LH levels, testicular mass on exam, and nonrevealing adrenal workup leading to testicular imaging and relevant elevated tumor markers (lactate dehydrogenase, alpha-fetoprotein, and beta-human chorionic gonadotropin [β-HCG]) ultimately revealed the diagnosis [ 22-24 ].…”
Section: Gender-affirming Hormone Therapy Preparationsmentioning
confidence: 99%